2021
DOI: 10.1002/cjp2.210
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of patient‐derived xenograft engraftment in pediatric sarcomas

Abstract: The goals of this work were to identify factors favoring patient-derived xenograft (PDX) engraftment and study the association between PDX engraftment and prognosis in pediatric patients with Ewing sarcoma, osteosarcoma, and rhabdomyosarcoma. We used immunodeficient mice to establish 30 subcutaneous PDX from patient tumor biopsies, with a successful engraftment rate of 44%. Age greater than 12 years and relapsed disease were patient factors associated with higher engraftment rate. Tumor type and biopsy locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
(77 reference statements)
3
6
0
Order By: Relevance
“…Evaluation of tumor volume during 21 days after the beginning of the treatment showed a higher response of EwS compared to non-EwS models (Fig. 1C), which is concordant with the potent activity of irinotecan in Ewing sarcoma PDXs 28 . When calculating tumor growth inhibition compared to tumor volume at the end of treatment (day 14), we found that growth inhibition was significantly higher in EwS PDX models (92.83%) compared to OS (33.67%) and UPS (-17.02%) (Fig.…”
Section: Ews Cell Lines and Tumors Are Highly Sensitive To Top1 Poisonssupporting
confidence: 76%
“…Evaluation of tumor volume during 21 days after the beginning of the treatment showed a higher response of EwS compared to non-EwS models (Fig. 1C), which is concordant with the potent activity of irinotecan in Ewing sarcoma PDXs 28 . When calculating tumor growth inhibition compared to tumor volume at the end of treatment (day 14), we found that growth inhibition was significantly higher in EwS PDX models (92.83%) compared to OS (33.67%) and UPS (-17.02%) (Fig.…”
Section: Ews Cell Lines and Tumors Are Highly Sensitive To Top1 Poisonssupporting
confidence: 76%
“…The analysis of clinico-pathological characteristics indicated a strong correlation between PDX establishment and patients OS, as already reported in another pediatric sarcomas platform. 23 Indeed, grafted PDXs were derived mainly from patients with very aggressive tumors. We observed a higher take rate for fusion-positive ARMS compared to ERMS, further suggesting that a more aggressive RMS histology is more likely to successfully grow in mice.…”
Section: Discussionmentioning
confidence: 99%
“…for peritoneal sarcomatosis (127,128)]. Although certainly technically challenging to establish, both heterotopic and orthotopic PDX models should be regarded as reference mouse RMS models due to their potential to maintain human tumor architecture, intratumoral and interpatient heterogeneity, and tumor microenvironment components, enabling their multipurpose use across various application areas (113,(129)(130)(131)(132). Figure 6 illustrates the process of selecting the preclinical mouse model based on specific utilization areas.…”
Section: Selection Of An Appropriate Mouse Model To Study Rmsmentioning
confidence: 99%